Characterizing masticatory motion of dogs using optical and electromagnetic motion tracking - Goldschmidt, Stephanie; Chew, Hooi Pin; Guy, Stephen; Fok, Alex (Frontiers in Veterinary Science, 2025)
IntroductionAccurate knowledge of masticatory motion across a variety of food materials is essential for ex-vivo testing and simulation of the food-teeth interaction. Yet, the masticatory motion has never been fully characterized in the domestic dog (Canis lupus), limiting our ability for ex-vivo modelling.ObjectiveThe aim of this study was to characterize masticatory motion among a variety of different foods in beagle dogs using optical and electromagnetic motion tracking.ResultsWe confirmed that the masticatory pattern in the beagle is a hinge motion with no clinically meaningful horizontal motion of the mandible. The mouth opening was not significantly difference among different food and treat types regardless of food stiffness and force to fracture of the food, with a mean and standard deviation of 2.51  ±  0.33 (range 1.93–2.95) cm between the canine teeth during chewing. Conversely, frequency of chewing was influenced by food type, with kibbles having a significantly higher peak mean chewing frequency (2.93 Hz) compared to other feeds. Frequency of chewing was linearly correlated to the force to fracture of the food material (p = 0.03, R2 = 0.56), while stiffness of food did not significantly affect peak chewing frequency.ConclusionData from this study can guide ex-vivo modelling of the feed-teeth interaction for product design and testing, especially those that focus on prevention of periodontal disease and dentoalveolar trauma.